Portfolio Choice with Non-Fungible Brokerage Cash - He, Xindi; Zhu, Ning (Journal of Financial and Quantitative Analysis, 2026)
An abstract is not available for this content so a preview has been provided. Please use the Get access link above for information on how to access this content.